Wise in Using Social Media: Education for Pahandut Residents of Palangkaraya - Achmadi Achmadi; Sanawiah Sanawiah; M. Arni (Universitas Muhammadiyah Sidoarjo, 2023)
There have been complaints and reports to the police related to the increase of alleged violations in the use of social media such as defamation, hate speech, hoax, data theft, illegal data distributions, and racial issues. The method used in this research is an observation done by conducting a survey through which a team visits and meets the residents of Pahandut Village to find out their lack of understanding of the ITE (Electronic Information and Transactions) Law. The researchers found out that the residents have various interpretations of the ITE Law. Therefore, the researchers need to focus on the important issue and conduct socialization for them by educating families to cope with the problem. In the first phase, education can be done by avoiding provocative themes, checking sources of information and their authenticity, and thinking before sharing. The act of community empowerment in Pahandut Village and its Muhammadiyah residents as da'wah agents are the targets of community service activities. The result of this community service activity is the successful socialization and education concerning the ITE Law to the residents of Pahandut Village. The success of residents’ satisfaction level is measured by the high percentage of the residents who choose very important indicators in community service. The socialization of the ITE Law and education to the community is carried out through community service videos containing stories about families who use their social media wisely.